FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Nova Hari Setyawan; Riana Rachmawati Dewi (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2021)
This study aims to examine and analyze the effect of profitability, company size, auditor reputation and leverage in automotive and component manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2012-2019. Profitability as measured by ROA on audit delay, the effect of company size as measured by size on audit delay, the effect of auditor reputation as measured by dummy variables on audit delay, the effect of leverage as measured by DER on audit delay. The data analysis technique in this research is multiple linear regression. The sampling method was purposive sampling, with the number of samples used by 32 companies that had met the criteria for determining the sample. Based on the analysis, it can be concluded that the variables of profitability, firm size, auditor reputation and leverage partially and simultaneously have an effect on audit delay. Keywords: Profitability, Company Size, Auditor Reputation, Leverage, Audit Delay